2004
DOI: 10.1016/j.ultras.2003.11.015
|View full text |Cite
|
Sign up to set email alerts
|

Sonographic evaluation of subacromial space

Abstract: Goal of the study. The purpose of this study is to compare the accuracy of sonographic to radiographic measurements of subacromial space, and verify its variations in relation to acromial morphology, age, sex and rotator cuff pathologies. Materials and methods. As a result, we have compared a radiographic examination to sonographic examination, each measuring the subacromial space in 200 random shoulders, with a personal method. The sonographic examination was performed by using a HDI 5000 ultrasound scanner S… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

6
69
1
1

Year Published

2007
2007
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 64 publications
(78 citation statements)
references
References 7 publications
(7 reference statements)
6
69
1
1
Order By: Relevance
“…These previous studies have measured the subacromial space under in-vivo conditions with various imaging modalities, including three-dimensional (3D) computed tomography (Lochmuller et al, 1997), clinical radiographs (van de Sande and Rozing, 2006,van de Sande et al, 2006,Lehtinen et al, 2000,Petersson and Redlund-Johnell, 1984, ultrasound imaging (Girometti et al, 2006,Azzoni et al, 2004, and MRI (Pappas et al, 2006,Graichen et al, 1998,Graichen et al, 1999b,Graichen et al, 1999a,Graichen et al, 2001,Graichen et al, 2005,Hinterwimmer et al, 2003,Roberts et al, 2002,Solem-Bertoft et al, 1993. Additional studies have estimated the subacromial space width based on shoulder kinematics as measured using skin-mounted sensors (Tsai et al, 2003,Thigpen et al, 2006,Ludewig and Cook, 2002,Nawoczenski et al, 2003.…”
Section: Introductionmentioning
confidence: 99%
“…These previous studies have measured the subacromial space under in-vivo conditions with various imaging modalities, including three-dimensional (3D) computed tomography (Lochmuller et al, 1997), clinical radiographs (van de Sande and Rozing, 2006,van de Sande et al, 2006,Lehtinen et al, 2000,Petersson and Redlund-Johnell, 1984, ultrasound imaging (Girometti et al, 2006,Azzoni et al, 2004, and MRI (Pappas et al, 2006,Graichen et al, 1998,Graichen et al, 1999b,Graichen et al, 1999a,Graichen et al, 2001,Graichen et al, 2005,Hinterwimmer et al, 2003,Roberts et al, 2002,Solem-Bertoft et al, 1993. Additional studies have estimated the subacromial space width based on shoulder kinematics as measured using skin-mounted sensors (Tsai et al, 2003,Thigpen et al, 2006,Ludewig and Cook, 2002,Nawoczenski et al, 2003.…”
Section: Introductionmentioning
confidence: 99%
“…1,15,19 Studies using ultrasound imaging corroborate these findings with a smaller AHD in patients with RCD 3,14 and a smaller AHD with increased severity of the RCD. 3 Although these studies consistently indicated a smaller AHD with RCD, they varied on the location of the measurement of the SAS. MRI studies 1,15,19 depicted the location as the anterior to middle aspect of the SAS, or at the location of the small- used as described in this study, using the same investigator to collect data and make AHD measurements.…”
mentioning
confidence: 96%
“…Studies using ultrasound imaged the SAS over the middle SAS space, 2,3 or did not state the exact location of the ultrasound transducer during imaging.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Azzoni et al (2004) stated that the severity of rotator cuff pathologies is directly proportional to the decreasing magnitude of the subacromial space. The rhomboidal and triangular subacromial spaces as reported by Sperner (1995) were identified in this study.…”
Section: Morphology Of the Acromion And Subacromial Spacementioning
confidence: 99%